2004
DOI: 10.1136/jech.2003.014308
|View full text |Cite
|
Sign up to set email alerts
|

Linking perceptions of neighbourhood to health in Hamilton, Canada

Abstract: Study objective: To investigate the association between perceptions of neighbourhood physical and social characteristics and three health outcomes (self assessed health status, chronic conditions, and emotional distress). Design: Cross sectional survey data analysed in small neighbourhoods. Setting: Hamilton, Ontario, Canada, a medium sized industrial city, located at the western end of Lake Ontario (population at the time of the study about 380 000). Participants: Random sample of 1504 adults aged 18 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 33 publications
4
68
0
2
Order By: Relevance
“…Operationalizing specific measures of the characteristics of local areas hypothesized to be important for living a healthy life provides a more focused approach than general measures of deprivation in the search for area effects 26 . Thus, more emphasis should be given to residents' perceptions of physical environmental factors in the formulation of local public health polices 45 . Contributors D. A. Höfelmann participated in the study design, including data quality control, supervised the fieldwork activities, performed the multilevel analysis of the data, and was responsible for the study's analytic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Operationalizing specific measures of the characteristics of local areas hypothesized to be important for living a healthy life provides a more focused approach than general measures of deprivation in the search for area effects 26 . Thus, more emphasis should be given to residents' perceptions of physical environmental factors in the formulation of local public health polices 45 . Contributors D. A. Höfelmann participated in the study design, including data quality control, supervised the fieldwork activities, performed the multilevel analysis of the data, and was responsible for the study's analytic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…As Cummins, Curtis, Diez-Roux, and argue, information is required concerning the time of exposure to different contexts in space and time, if the aim is to further our knowledge of environmental effects on health. Moreover, we are unable to measure residents' perceptions and reports, usually related with health and health-related behaviours (Van Lenthe et al, 2005;Wilson et al, 2004). Therefore, an effort must be made to generate and collect data concerning individual perceptions of neighbourhood, which can be achieved by integrating qualitative research into our quantitative approach.…”
Section: Limitationsmentioning
confidence: 99%
“…A study in China 21 showed that people with lower educational levels were more likely to fall ill. We found that subjects who rated their living conditions as poor were significantly worse off in terms of SRH, which is consistent with previous studies investigating the link between neighborhood perception and subjective health status. 22,23 The causal mechanisms underlying social inequalities in health are complex. 4,24 Causation could run from income to health or from health to income.…”
Section: Discussionmentioning
confidence: 99%